The Study Thainess culture within Western movies. - Kunmaneelert, Nawaphon (JOURNAL OF RATTANA PAÑÑĀ, 2020)
This article has the objective to study Thainess culture within Western movies. This article is qualitative research. Analyze the study results using the concept of Thai identity. From the 5 movie content which is The Hangover Part II, The Impossible, Only god forgives, Fast & Furious 7 and <a href="https://www.google.co.th/url?sa=t&rct=j&q=&esrc=s&source=web&cd=2&cad=rja&uact=8&ved=0ahUKEwinuuactYnWAhXJ6Y8KHfNsB4cQFgg5MAE&url=https%3A%2F%2Fwww.movie2free.com%2Fghost-house-%25E0%25B8%25A1%25E0%25B8%25B1%25E0%25B8%2599%25E0%25B8%25AD%25E0%25B8%25A2%25E0%25B8%25B9%25E0%25B9%2588%25E0%25B9%2583%25E0%25B8%2599%25E0%25B8%25A8%25E0%25B8%25B2%25E0%25B8%25A5%2F&usg=AFQjCNE-H2ElB4vYvmtWU1FJeHICix3knw">Ghost House. The results showed that the Thainess culture in all 5 Western movies Can be divided into 10 issues include 1) Language 2) Fine arts 3) Religion and beliefs 4) Values ​​5) Way of life 6) Traditions 7) Food 8) Thai sports 9) Superstition belief 10) Other Thai styles and 11) Martial arts. In addition, it is found that the content of western movies that is presented is simple human and all around. And all 5 Western movies used in the study have demonstrated social characteristics and Thai culture in similar aspects. Including the characteristics of the presentation are similar. Including the characteristics of the presentation, there are still similarities